THE EFFECT OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY IN USERS OF J&T EXPRESS SERVICE IN THE SURAKARTA - Sejati, Septy Agil (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This study aims to analyze the effect of service quality (X) and customer satisfaction (Z) on customer loyalty (Y) for J&T Express service users in the Surakarta Residency. The population in this study were J&T Express service users in the Surakarta Residency and obtained a sample of 90 respondents using the Purposive Sampling technique. The data collection method uses a questionnaire and is processed using Partial Least Square (PLS) analysis with SmartPLS 3.0 software. The results of this study indicate that service quality has a significant positive effect on customer satisfaction, customer satisfaction has a significant positive effect on customer loyalty, service quality has a significant positive effect on customer loyalty, and service quality has a significant positive effect on customer loyalty mediated by customer satisfaction.